Factors that Promote or Hinder a Youth In Care Network: A Report from the Field - Keller, Amanda; Doucet, Melanie; Dupuis, Jennifer; Dupuis, Jessica; Mann-Feder, Varda (International Journal of Child, Youth and Family Studies, 2020)
This report describes the evolution of an independent youth-led organization for youth in and from care in Quebec. The emergence of CARE Jeunesse is presented and compared with two other networks in Canada. Factors that promoted and hindered its development are discussed particularly as they apply to issues outlined in the youth engagement literature. The board of CARE Jeunesse, comprising former youth in care, wrote this article with the participation of a university professor who is an adult ally to the alumni of care movement in Quebec. This report is the first publication that provides an account of the processes associated with developing a youth in care network in Canada.